Distribution of the tetracycline resistance determinant tetQ gene in oral isolates of black-pigmented anaerobes in Japan - Okamoto, M; Takano, K; Maeda, N (Oral microbiology and immunology, 2001)
We investigated the distribution of tetracycline resistance determinant tetQ in oral black-pigmented anaerobes using a polymerase chain reaction (PCR) METHOD: A total of 185 healthy subjects were divided into 3 groups based on subject age: young (6 to 10 years, n=58), middle (11 to 40 years, n=96), and elder (exactly 70 years, n=31). The prevalence of black-pigmented anaerobes in the gingival sulcus among these groups was 29.3%, 28.2%, and 64.5%, respectively. The prevalence of Prevotella nigrescens among these groups was 22.4%, 15.6%, and 32.3%, respectively, whereas the prevalence of Prevotella intermedia was 1.7%, 4.2%, and 35.5%, respectively. Porphyromonas gingivalis was found only in the elder group (16.1%). The prevalence of the tetQ gene in the black-pigmented anaerobes-positive subjects was almost the same among the 3 groups (approximately 30%). The tetQ gene was found in 27.5% (46 of 167) of P. nigrescens isolates, whereas it was found in only 6.4% (3 of 47) of P. intermedia isolates and in none of the 19 P. gingivalis isolates. Restriction endonuclease digestion patterns of the PCR products revealed 83.6% of 49 tetQ-positive isolates were of subtype A2H2 (AluI type 2, HpaII type 2).